Evaluate kx (x - 2) + 6 = 0

Given equation is: kx (x−2) + 6 = 0

kx2 − 2kx + 6 = 0

Then a=k, b = −2k , c = 6

Then b2 − 4ac = 0

So (−2k)2 − 4k(6) = 0

4k2 − 24k = 0

4k(k−6) = 0

k = 0 and k = 6

Put value of k

Then 6×2 − 12x + 6 = 0

6×2 − 6x − 6x + 6 =0

6x (x−1) − 6(x−1) = 0

∴x = 1

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question